The SEC revolving door and comment letters - SHEN, Michael (Institutional Knowledge at Singapore Management University, 2023)
Government officials, advocacy groups, and the business press have raised concerns that former SEC employees may continue to influence the SEC after leaving the agency. Using hand-collected data on the characteristics of 1,384 lawyers who represented firms in responding to SEC comment letters between 2005 and 2016, we examine the impact of post-revolving SEC employees on the SEC comment letter process. Among other determinants, we find that older and larger firms with a history of litigation are more likely to hire former SEC lawyers over non-SEC lawyers. Relative to firms that involve only non-SEC lawyers, we find that firms that involve former SEC lawyers in responding to SEC comment letters negotiate to a greater extent with the SEC, and have a lower likelihood and number of amendment filings, after matching on lawyer, law firm, comment letter, and firm characteristics.